Kajian Filosofi Tari Gandrung Dalam Upacara Ngusaba Nini Di Desa Adat Kekeran, Kecamatan Busungbiu, Kabupaten Buleleng - Gd Arya Krishna Duta Putra Tuboeh; I Wayan Gata; I Wayan Kariarta (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2022)
Kekeran Traditional Village located in the Busungbiu District, Buleleng Regency. The Kekeran Traditional Village has a unique culture and is hereditary in the form of the Gandrung dance which is staged during the ngusaba nini ceremony. The formulation of the problem related to this research is 1) the form of the Gandrung dance performance in the Kekeran Traditional Village, 2) the function of the Gandrung dance performance in the ngusaba nini ceremony in the Kekeran Traditional Village, 3) the philosophical meaning of the Gandrung dance in the ngusaba nini ceremony in the Kekeran Traditional Village, Busungbiu District, Buleleng Regency. The results of this study include: 1) From the aspect of the form of Gandrung dance performances in the ngusaba nini ceremony, they include: Mabyakala, Majaya-jaya, Mepiuning, and Gandrung dance performances. 2) From the aspect of function, it includes: social functions, namely holding interactions and establishing brotherly relationships, cultural preservation functions, namely as a hereditary cultural heritage that must be preserved and staged to maintain the noble values of the culture of the Kekeran Traditional Village, and religious functions, namely as an expression of gratitude for the community. for the abundant harvest in the Kekeran Traditional Village. 3) From the aspect of philosophical meaning including aesthetic meaning which is found in the Gandrung dance dress as a symbol of banten gebogan (pajegan) which can create an atmosphere of happiness, and the meaning of education is found in the performance during the ngusaba nini ceremony which teaches life to always be simple, low self-esteem, and humble and appreciate the services of the farmers who have taken care of and care for the crops found in the Kekeran Traditional Village.